Die grondwet as gedenkteken en die werkdadigheid van onopvallende, grondwetlike kragte - Plessis, L. du (Koers, 2005)
Memorialising a constitution: the power of unspectacular constitutional forces Annette Combrink’s appointment as rector of the (new) North- West University’s Potchefstroom Campus is telling of modest beginnings – for both the North-West University as a new institution and for the “principle of CHE” in terms of which the previous Potchefstroom University asserted the right to be a confessional university with a Christian-Reformational (or Calvinistic) profile. The point of this article is that modest beginnings need not be equated with weakness, inconsequeuntialness or failure: strength is often to be found not (only) in the spectacular, the ostentatious and the triumphant, but (also) in the unspectacular, the unassuming and the restrained. This point is illustrated by the various modes of functioning of South Africa’s constitution in protecting fundamental rights. Such (contrasting) modes of functioning are investigated and assessed in this article.